2013
DOI: 10.1007/s10620-013-2811-x
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Melatonin on Plasma Markers of Inflammation and on Expression of Nuclear Factor-Kappa Beta in Acetic Acid-Induced Colitis in the Rat

Abstract: Melatonin is effective in prevention and short-term treatment of the inflammatory process in acetic-acid induced colitis whereas the benefit of long-term treatment is unclear. Benefit may be linked to protection mechanisms against inflammatory processes by inhibiting the nuclear factor-kappa beta and conserving endogenous antioxidant reserves of total thiols, thus reducing the level of colonic damage possibly caused by lipid peroxides.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Recently, it was shown that very high doses of melatonin reduce epithelial paracellular permeability in rats and may prevent deleterious substances such as endotoxins from leaking in and causing inflammation [ 51 ]. An alleviating role has been ascribed to melatonin in the elusive interplay between different aggressive and protective factors in experimental colitis [ 52 54 ]. We tested the hypothesis that melatonin receptors and enzymes needed for synthesis may be up-regulated in inflammatory bowel disease compared to controls but found no large differences in mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was shown that very high doses of melatonin reduce epithelial paracellular permeability in rats and may prevent deleterious substances such as endotoxins from leaking in and causing inflammation [ 51 ]. An alleviating role has been ascribed to melatonin in the elusive interplay between different aggressive and protective factors in experimental colitis [ 52 54 ]. We tested the hypothesis that melatonin receptors and enzymes needed for synthesis may be up-regulated in inflammatory bowel disease compared to controls but found no large differences in mRNA expression.…”
Section: Discussionmentioning
confidence: 99%
“…In this systematic review, 101 different substances/live organisms/functional foods with antioxidant capacity, principally for UC, were identified. However, few compounds were tested more than once, including: the angiotensin II receptor antagonist [99] , [100] , [233] ; the inhibitors of hydroxymethylglutaryl COA reductases [101] ; the hormone MEL [96] , [103] , [109] , [234] ; the synthetic substances N -acetylcysteine [120] , [235] , [236] , [237] , [238] , bis(1-hydroxy-2,2,6,6-tetramethyl-4-piperidinyl)decandioate [239] , [240] and 3,4-oxo-isopropylidene-shikimic acid [241] , [242] , [243] ; resveratrol, some of its derivatives [137] , [138] , [140] , [141] , [142] , [143] , [244] and curcumin [151] , [152] , [153] , [154] ; the flavonoids proanthocyanidin from grape seeds [85] , [165] , [166] ; quercetin [155] , [156] ; coumarin derivatives [76] , [245] , [246] ; the microalga spirulina [247] , [248] ; active compounds such as cannabigerol [179] and cannabidiol [180] from Cannabis sativa [179] , [180] , which hampered the performance of a meta-analysis.…”
Section: Conclusion and Future Perspectivesmentioning
confidence: 99%
“…5-HT is an important compound derived from Trp which serves as a neurotransmitter and inhibiter of the production of inflammatory cytokines and superoxide [46]. MT is abundant in gastrointestinal tract [68, 69] and has a positive impact on IBD with no or negligible side effects due to regulation of macrophage activity, reduction of cell migration and myeloperoxidase activity, and inhibition of NF- κ B and TNF- α expression [36, 68, 70]. MT added to omeprazole treatment obviously accelerates chronic gastroduodenal ulcers over the obtained with omeprazole alone [71].…”
Section: Amino Acids: Application In Inflammatory Bowel Disease Thmentioning
confidence: 99%